Impact of plot size on tropical forest structure and diversity estimation - Silveira, Alan Bernardes da; Carvalho, Samuel de Padua Chaves e; Nicoletti, Marcos Felipe; Silva, Carlos Alberto; Drescher, Ronaldo; Carvalho, Mariana Peres de Lima Chaves e; Madi, Joao Paulo Sardo; Topanotti, Larissa Regina; Zeviani, Walmes Marques; Andrade, Valdir Carlos Lima de (Revista de Biología Tropical, 2022)
Introduction: Inventories are essential for forest management, but, in the Amazon region, the absence of standardization produces information loss, low accuracy, and inconsistent measurements. This prevents valid comparisons and compromises the use of information in networks and software. Sampling unit size is of key importance in the inventory of native forests, particularly regarding accuracy and costs. Objective: To identify a plot size that provides adequate precision for dendrometric parameters in the Amazon. Methods: In Cotriguaçu, Mato Grosso, Brazil, we tested four plot sizes with six repetitions each: 2 500, 5 000, 7 500, and 10 000 m². We measured diameter at breast height, population density, basal area, and biomass. We applied Shannon and Jaccard indexes; Weibull 2P and Gamma functions to fit the diametric distribution; and the Akaike Information Criterion for the best model. Results: There was a directly proportional relationship between plot area and population similarity, but diversity did not indicate significant alterations. Plot size did not affect dendrometric attributes and diametric distribution. Larger plot areas led to lower coefficients of variation and smaller confidence intervals. The Gamma function was the best model to represent the distributions of different plot sizes. Conclusions: For similar forests, we recommend the 2 500 m² plot to evaluate diameter at breast height, population density, basal area, and biomass.